Primary eye care for the general practitioner - V. Thunström (South African Family Practice)
This article outlines the clinical features and management of the basic eye conditions that every general practitioner should be able to diagnose and treat. These include ocular and adnexal conditions such as stye, conjunctivitis, blepharitis and preseptal cellulitis. The more severe conditions, such as dacryocystitis, corneal ulcer and orbital cellulites, also are presented, along with the criteria for specialist referral.